Pengaruh Jarak Sumber Pencemar Terhadap Kada Sulfat (SO4) pada Debu Terendap di Sepanjang Jalan Angkut Batubara - Tiara Pratiwi; Junaidi Junaidi; Zulfikar Ali As (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2017)
Abstract: The Influence Of The Distance Of Pollutant Source On Sulfate (So4) Concentrations In The Dust Along The Coal Haul Road. One of the quality parameters of coal is Sulfur. Sulfur content in coal be able to reach 4%. Sulfur content in coal at South Kalimantan mine ranges from 0.08 – 1.58%. Sulfur can be in the form of pyrite as S2 and sulfate as SO4. Sulfur content in coal dust that floats in the air will fall along with rain. This study aims to determine the effect of distance to SO4 levels on dust along coal haul roads. The sampling point was taken from variation of distance that is 1 m, 50 m, 100 m, 150 m, and 200 m from the side of coal haul road. The results showed that the highest sulfate concentration was at 1 m distance from the side of the road, that was 37.865 mg/L, and the lowest was at 200 m distance from the side of the road, that was 3.405 mg/L. These sulfate concentrations were proportional to dust fall. The farther the sampling point, the sulfate content decreases. Keywords: Dust Fall; sulfate concentration; distance.